ORGANIZATIONAL COMMITMENT AS A MEDIATOR: EMPIRICAL ANALYSIS OF TRANSFORMATIONAL LEADERSHIP, JOB SATISFACTION AND PERCEIVED ORGANIZATIONAL SUPPORT ON TURNOVER INTENTION - Adiansyah; Ervin Nora Susanti; Herni Widiyah Nasrul (RADJA PUBLIKA, 2026)
This study investigates the role of organizational commitment as a mediating variable in the relationship between transformational leadership, job satisfaction, perceived organizational support (POS), and turnover intention. Using a quantitative cross-sectional design, data were collected from employees through structured questionnaires. The findings reveal that transformational leadership, job satisfaction, and POS significantly influence turnover intention both directly and indirectly. Organizational commitment plays a crucial mediating role, indicating that employees with stronger emotional attachment to their organization are less likely to leave. Transformational leadership enhances motivation and engagement, while job satisfaction and POS foster positive employee attitudes and perceptions. The study contributes to the literature by integrating multiple predictors into a comprehensive model and highlighting the importance of mediation analysis. Practically, the results suggest that organizations should strengthen leadership practices, improve job satisfaction, and enhance organizational support to reduce turnover intention and improve retention.